Morphology and Distribution of TDP-43 Pre-inclusions in Primary Progressive Aphasia - Kim, Garam (J Neuropathol Exp Neurol, 2019)
Diffusely stained phosphorylated 43-kDa TAR DNA-binding protein (TDP-43)-positive “pre-inclusions” have been described. This experiment investigated morphological subtypes of pre-inclusions and their relationship with TDP-43 inclusions in primary progressive aphasia (PPA), a dementia characterized by gradual dissolution of language. Brain sections from 5 PPA participants with postmortem diagnoses of frontotemporal lobar degeneration with TDP-43 pathology (FTLD-TDP) were immunohistochemically stained using an antibody to phosphorylated TDP-43 and quantitatively examined for regional and hemispheric distribution using unbiased stereology. Cortical TDP-43 pre-inclusions included smooth, granular/dot-like, or fibrillar staining with localization to the nucleus, cytoplasm, or both. Mature and pre-inclusions were quantified in a region with high and a region with low mature inclusion density, and contralateral homologs. Regions with lower mature inclusions were characterized by higher densities of pre-inclusions, while increasing burden of inclusions corresponded to lower densities of pre-inclusions (p < 0.05). Mature inclusions showed significant asymmetry that favored the language-dominant hemisphere (p < 0.01), while pre-inclusions displayed the opposite pattern (p < 0.01). Granular-type pre-inclusions were more abundant (p < 0.05) and drove the hemispheric and regional differences (p < 0.02). These results suggest that pre-inclusions are present in greater abundance prior to the formation of mature TDP-43 inclusions, and appear to develop through progressive stages into mature intracytoplasmic, or intranuclear aggregates.